Forecasting Gross Written Premiums in Albania’s Life Insurance Industry: Insights for Financial Sustainability - Kopani, Albion; Kopani, Xhevdet (European Journal of Sustainable Development, 2025)
The insurance industry in Albania is a sector that consistently receives significant attention in the overall financial industry and plays a crucial role in fostering a culture of insurance among the populace. Year after year, these companies have expanded their presence to the clients, and what is most important, they have expanded the products that they are selling to the clients. This paper aims to analyze the historical development trends of the Albanian insurance industry, taking into account its significance for a developing economy. Additionally, empirical models will be constructed to predict the values of gross written premiums over a four-year period. The methodology that will be used consist of the analyses of SARIMA and Holt-Winter models to prevent the prediction of the four year period on gross written premiums (GWP) on the life insurance industry in Albania. These models and the comparison between them will prevent a better understanding of the future life insurance in Albania. Those results will help all participant actors of the industry to contribute to a safe and secure environment for the people. Also, the result will help to see the trend and lead the government and companies to prevent the impact of economic sustainability. The conclusion from this paper is that the years from 2024 to 2027 life insurance will grow Keywords: Life Insurance, analysis, SARIMA, Holt-Winters, safe environmental, GWP, Albania.